Strategi Penguatan Wawasan Kebangsaan bagi Mahasiswa Program Studi Pendidikan Pancasila dan Kewarganegaraan Fakultas Keguruan dan Ilmu Pendidikan Universitas Nusa Cendana - Kamlasi, Anjulin Yonathan; Utami, Tri (Universitas Nusa Cendana, 2025)
The lack of understanding of national insight among the younger generation, amid the rapid pace of globalisation and developments in information technology, poses a major challenge to the continued integrity of the nation and state. The strategy to strengthen national awareness among students of the Pancasila and Citizenship Education Study Programme (PPKn) at the Faculty of Teacher Training and Education (FKIP) of Nusa Cendana University (Undana) is a concrete step in shaping national character and increasing students' awareness of nationhood and statehood. The purpose of this study is to analyse the strategy for strengthening of national awareness among students of the PPKn programme at FKIP Undana. The method used in writing this article is descriptive qualitative, with an emphasis on library research. Library research is a method of data collection by reviewing and analysing various relevant written sources, such as books, journals, and documents, in order to gain a general understanding and theoretical basis of the topic being studied. The results of the study show that the strategy for strengthening the national awareness of students in the PPKn FKIP Undana study programme is carried out through various activities such as integration into the curriculum, extracurricular activities and student organisations, active involvement in community service activities, and the use of technology and social media. Through these various activities, students not only understand national values theoretically, but are also able to apply them and become agents of change who can implement national values in social and educational life.